Development and validation of an Industry 4.0 adaptation potential scale (4IRAPS) - Sözbilir, Fikret (Technological and Economic Development of Economy, 2021)
The aim of this study was to develop a scale that can measure the potential of adapting to Industry 4.0, which refers to the fourth industrial revolution described as a combination of the innovation of various digital technologies rapidly developed in recent years. In addition, the reliability and validity of the Industry 4.0 Adaptation Potential (4IRAPS) is demonstrated. This research was conducted in two stages of a pilot and a main study. The data was collected from 174 participants enrolled in technical and management departments at the graduate and associate degree levels of two different universities. A 50-item questionnaire concerning Industry 4.0 prepared by experts experienced in this field was applied to the participants. As a result of a factor analysis, 30 items and 11 subscales with low a factor load and reliability level were removed from the questionnaire. The reliability and validity of 4IRAPS were verified by” the analyses via PLS-SEM. Finally, the remaining four sub-dimensions referring to Industry 4.0 were labelled as interested, effort for adaptation, readiness, and pessimism. This study developed the first scale of the industry 4.0 adaptation potential. The scale consists of four sub-dimensions and 17 items. It was determined that this scale was statistically reliable and valid. First published online 23 March 2021